Greenspace, urbanity and health: relationships in England - Mitchell, Richard (BMJ Group, 2007)
OBJECTIVES: To determine the association between the percentage of greenspace in an area and the standardised rate of self‐reported “not good” health, and to explore whether this association holds for areas exhibiting different combinations of urbanity and income deprivation. DESIGN AND SETTING: Cross‐sectional, ecological study in England. PARTICIPANTS: All residents of England as at the 2001 Census. MAIN OUTCOME MEASURES: Age and sex standardised rate of reporting “not good” health status. RESULTS: A higher proportion of greenspace in an area was generally associated with better population health. However, this association varied according to the combination of area income deprivation and urbanity. There was no significant association between greenspace and health in higher income suburban and higher income rural areas. In suburban lower income areas, a higher proportion of greenspace was associated with worse health. CONCLUSIONS: Although, in general, higher proportion of greenspace in an area is associated with better health, the association depends on the degree of urbanity and level of income deprivation in an area. One interpretation of these analyses is that quality as well as quantity of greenspace may be significant in determining health benefits.